President of the Sami Parliament Address to the UNPFII - Olli, Egil (2009)
United Nations Permanent Forum on Indigenous Issues is currently going on in New York (18th – 29th May). First out to give a statement from the Norwegian delegation was President of the Sami Parliament in Norway, Egil Olli. 20/05/2009 :: Madam Chair, Let me at the outset express the Sami Parliaments satisfaction of letting us host The Permanents Forums presessional meeting in March this year. At the same time I should also express our satisfaction to the Norwegian Government that made this possible by their financial contributions. In my opinion it is urgent that the UN Permanent Forum in this way may get the possibility to observe how different Indigenous people live and our lively conditions. The Sami material and social situation is in some regard better than for many other indigenous peoples throughout the world. This is a fact we could be satisfied with. At the same time, we have to accept that these facts create responsibilities to act on behalf of those less fortunate. We, the Sami, have in our struggle for better living conditions, recognition and fight for rights sought to solve our problems through dialog and compromises. This has also been the strategy of the Sami Parliament science it was established in 1989. We have put our faith in the belief that our needs and claims could be solved in ways that give us the necessary recognition as indigenous people in Norway and in the Nordic states. We claim acceptance for our own culture, our language and our strong relations to our traditional territories. We state as basic that our special interests and needs shall be established within long-term perspectives and be recognized in the legislation of the state and in the administrative system. The Sami Parliament has previously informed the Permanent Forum that we in this respect has engaged in an agreement with the Government on procedures for consultations on actions or legislation that have an impact on Sami interests.